Methane Emission Reduction and Biological Characteristics of Landfill Cover Soil Amended With Hydrophobic Biochar - Qin, Yongli; Xi, Beidou; Sun, Xiaojie; Zhang, Hongxia; Xue, Chennan; Wu, Beibei (Frontiers in Bioengineering and Biotechnology, 2022)
Biochar-amended landfill cover soil (BLCS) can promote CH4 and O2 diffusion, but increases rainwater entry in the rainy season, which is not conducive to CH4 emission reduction. Hydrophobic biochar-amended landfill cover soil (HLCS) was prepared to investigate the changes in CH4 emission reduction and biological characteristics and BLCS as control. Results showed that rainwater retention time in HLCS was reduced by half. HLCS had a higher methane reduction potential, achieving 100% methane removal at 25% methane content of landfill gas, and its main contributors to methane reduction were found to be at depths of 10-30 cm (upper layer) and 50-60 cm (lower layer). The relative abundances of methane-oxidizing bacteria (MOB) in the upper and lower layers of HLCS were 55.93% and 46.93%, respectively, higher than those of BLCS (50.80% and 31.40%, respectively). Hydrophobic biochar amended to the landfill cover soil can realize waterproofing, ventilation, MOB growth promotion, and efficient methane reduction.